KARAKTERISTIK HRS-WC DENGAN AGREGAT HALUS DISUBSTITUSI PASIR PANTAI - Purbanto, Raka; Thanaya, I Nyoman Arya; Saraswati, AA Istri Rara Anggita (Jurnal Ilmiah Teknik Sipil, 2023)
The availability natural sand is increasingly limited, thus beach sand can be as an alternative substitute to fine aggregate for asphalt mixture, where asphalt can undergo ageing. The purpose of this study was to analyze the characteristics of beach sand and HRS-WC mixture substituted with beach sand at Optimum Asphalt Content (OAC). The research begins with materials testing and manufacture of samples to obtain OAC. At OAC substitution of stone ash with 50% and 100% of beach sand was done based on volume on fine aggregate passing 2.36mm retained on 0.075mm. It was obtained that the characteristics of beach sand in general was not far different from natural sand, however. the angularity value of the beach sand was unfulfilled because the surface of the beach sand is extremely smooth. The characteristics of HRS-WC with beach sand substitution at 50% and 100% was obtained with marshall stability value of 2269,757kg and 2654,942kg; flow 1.062mm and 2.777mm; MQ 2156,120kg/mm and 957,308kg/mm; VIM 5.570% and 4.898% (close to minimum value); VMA 19.826% and 18.398%; VFB 71.908% and 73.375%. The marshall characteristics of the samples conditioned on STOA, LTOA 2 days and LTOA 5 days met the specification. The Cantabro test values under normal conditions, STOA, LTOA 2 days and LTOA 5 days with 50% beach sand were: 4.284%, 3.942%; 1.977%, 1.451%; and with 100% beach sand were: 6.067%; 5.758%; 4.101%; and 3.366% (< the recommended value of 16%). In general the characteristics of the mixture met the specification, just on the mixture with 100% sand beach, the VIM was close to minimum value